Análise acústica das distorções vocais intencionais produzidas por cantores de rock - Fiuza, Mauro Barro (2018)
Introduction: intentional voice distortion creates different vocal qualities that may even resemble to a dysphonic voice. This feature is used in singing as an element of expressiveness in several musical genres but are known as characteristics of rock. Studies have been done with the purpose to understand the ways these distortions are produced, but few sought to understand the acoustic variations of each vocal setting Objective: to analyze different intentional voice distortions in rock singers based on acoustic analysis. Method: eight singers, six men and two women, with an average age of 36 years old, who answered a survey in which they indicated the types of voice distortions they used. Then the following sound samples were collected: vowel emission [e], music section and sustained distorted voice for each of the previously listed types. Acoustic and visual-acoustic analysis were performed and the values of fundamental frequency, the vowel used in the sustained distortion, the spectrographic trace, the amount of sub-harmonics and the range of the harmonic component were extracted. The data of the distortions in the music section and sustained sample were compared and the spectrographic traces were classified according to the presence of harmonics and noise. Results: 47 types of distortions were collected. In 38 types there were only a small variation in the comparison between the samples of the adjustments in the music and sustained distortion. The types of spectrographic traces that mixed harmonics and noise were the majority, 37 of them in the music samples and 38 in the sustained ones. The most used vowels were intermediate (33) and anterior (32). Six types presented only noise and there was a variation in the number of sub-harmonics from zero to eight. Conclusion: of all the intentional voice distortions collected, the majority presented spectrographic traces with the presence of both harmonic and noise components, but with a great variation in the harmonic component ranges and the sub-harmonic ratio in relation to the fundamental frequency. Factors such as the chosen vowel and the fundamental frequency sung influenced the precision of the emission of the distortions, which evidenced the need to understand the specificities of each type. Similarity was also observed when comparing sustained distorted sounds and music sections